Evaluation of II. Abdulhamid and his period in terms of political Geography - KOCALAR, ALİ OSMAN (My University, 2023)
Political Geography is a branch of science that has started to make a name for itself, especially in the last years of the 19th century all over the world. Ottoman Sultan II. Abdulhamid Khan was the leading actor of the world political scene in those years. He was an important personage influencing world politics in the years when such a science emerged. Examining the II. Abdulhamid period will certainly attract attention. Socio-cultural power, which has an important place in political geography, the characteristics of the human who make up a nation are the power formed by educated people equipped with technical knowledge. In a sense, it means that the citizens of the state are well educated from the lowest level to the person who governs the state. From this point of view, Sultan II. Abdulhamid Han was a very perfect carpenter. He also used this carpentry profession in state administration. Because the job of the carpenter is to create perfect furniture sets from raw wood. While governing his state, he showed the whole world that the Ottoman Empire was not destroyed by correcting the unsound parts of the state. After he was dethroned, the collapse of the state accelerated, and those who dethroned him desired for him to come back to power.
Keywords: Political geography; Sultan II. Abdulhamid; geographical perspective; socio-cultural power